직교이방성 적층판의 Hole단부의 3D 비선형 층간응력 해석 - 송관형(KWAN-HYUNG SONG) (Han-guk haeyang gonghak hoeji (Online), 2004)
Orthotropic laminates, such as [$0^{\circ}6$/$90^{\circ}6$]s and [$90^{\circ}6$/$0^{\circ}6$]s, were performed, using a commercial nonlinear finite element method. Interlaminar stress distributions, around the hole curve free-edge, were calculated. The delamination bearing strengths of pin joints were predicted, using the modified delamination failure criterion. These stress distributions were presented along the radial lines and around the free-edge of the hole. Further, three-dimensional non-linear contact analysis of orthotropic laminates was conducted to investigate the effect of friction. In this paper, laminates with a circular hole were taken to study interlaminar stresses the curved edge. This study may assist in the design of a thick composite laminate with mechanically pin joints.